2021
DOI: 10.1089/jwh.2020.8807
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Financial Barriers to Cervical Cancer Screening and Associated Cost Burden Among Low-Income, Under-Screened Women

Abstract: Background: Despite screening's effectiveness in reducing cervical cancer incidence and mortality, disparities in cervical cancer screening uptake remain, with lower rates documented among uninsured and low-income individuals. We examined perceived financial barriers to, and the perceived cost burden of, cervical cancer screening. Materials and Methods: We surveyed 702 low-income, uninsured or publicly insured women ages 25-64 years in North Carolina, U.S., who were not up to date on cervical cancer screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…Despite high rates of health insurance coverage in our overall sample, including those who avoided healthcare for a year or more, cost was the most frequently cited reason for healthcare avoidance, followed closely by complexity and lastly, privacy. These results are consistent with previous findings that suggest cost and time are frequently reported barriers to accessing medical care [ 2 , 4 , 13 , 15 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite high rates of health insurance coverage in our overall sample, including those who avoided healthcare for a year or more, cost was the most frequently cited reason for healthcare avoidance, followed closely by complexity and lastly, privacy. These results are consistent with previous findings that suggest cost and time are frequently reported barriers to accessing medical care [ 2 , 4 , 13 , 15 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…major barriers to cervical cancer screening [14,15,22,37,38]. Our findings are consistent with results of a previous study using MBMT-3 data, which found that 72% of participants perceived financial barriers to screening and that uninsured women were more likely to perceive screening costs and follow-up treatment costs as barriers [39].…”
Section: Plos Onesupporting
confidence: 90%
“…Although routine cervical cancer screening is recommended and covered under the Affordable Care Act, a recent survey of 702 low‐income women who were uninsured or publicly insured demonstrated multiple perceived barriers to engaging in this crucial preventive service—with 72% citing financial barriers 21 . Persons without health insurance are less likely to be screened or vaccinated against HPV 22 …”
Section: Gaps In Screening and Preventionmentioning
confidence: 99%
“…20 Although routine cervical cancer screening is recommended and covered under the Affordable Care Act, a recent survey of 702 low-income women who were uninsured or publicly insured demonstrated multiple perceived barriers to engaging in this crucial preventive service-with 72% citing financial barriers. 21 Persons without health insurance are less likely to be screened or vaccinated against HPV. 22 Population characteristics, such as poverty and underinsurance or uninsurance, that place women at greater risk for cervical cancer are disproportionally concentrated in the less populated, rural areas of the United States.…”
Section: Gaps In Screening and Preventionmentioning
confidence: 99%